Analysis of Characteristics and Service Level Pedestrian Facilities in Region 5 Regional Military Night Market Surabaya - Fuji Dwi Setiawan; Atik Wahyu (Journal of World Conference (JWC), 2020)
Pedestrians are people walking activities and is one of the elements of road users. Surabaya is a city which is the goal of society to travel and enjoy a wide range of diversity with the intent to purchase goods or just taste the food because there is one of the traditional market situated on the road Raden Wijaya or road Kesatriyan very crowded at night ie the market night kodam v Surabaya and in the present study was to determine the characteristics of pedestrians (flow, speed, density), determine the relationship between variables pedestrian movement and maximum value of variables and determine the capacity and service level pedestrian with analytical methods in use that method Greenshields. This research method used survey methods and analysis methods. Ie survey method, uses manual techniques of observation and data collection in the field, while the analysis method is by using simple linear regression method in accordance with the method used by Greenshields. The analysis showed that the variable max on the Raden Wijaya is as follows Dm = 0.992 pends / m2, Vm = 66.787 m / min, Qm = 66.253 pends / min / m while the variable max on the road Kesatriyan is as follows Dm = 3.041 pends / m2, Vm = 37.398 m / min, Qm = 113.727 pends / min / m. While the level of service including service level "A", the standard planning pedestrian facilities in urban areas in the level of service "A", this means that the pedestrian in the night market kodam v Surabaya still meet the standards of planning and is still able to accommodate the number of pedestrians there is. While the correlation value on the road Raden Wijaya was r = -0.922 and correlation on the road Kesatriyan is r = -0.488.